Association between Ngb polymorphisms and ischemic stroke in the Southern Chinese Han population - Murong Shen-Xing; Xue Xie-Hua; Fang Ling; Lin Yi; Wang Ning; Wu Zhi-Ying (BMC, 2008)
Abstract Background Neuroglobin (Ngb), one of novel members of the globin superfamily, is expressed predominantly in brain neurons, and appears to modulate hypoxic-ischemic insults. The mechanisms underlying Ngb-mediated neuronal protection are still unclear. For it is one of the candidate protective factors for ischemic stroke, we conducted a case-control study to clarify the association of Ngb polymorphisms with ischemic stroke in the Southern Chinese Han population. Methods 355 cases and 158 controls were recruited. With brain imaging, cases were subdivided into large-artery atherosclerosis (LVD) and small-vessel occlusion (SVD) stroke. PCR amplified all the four exons of Ngb and flanking intron sequence for each exon. Genotyping for Ngb was achieved by direct sequencing and mismatched PCR-RFLP. Polymorphisms were studied both individually and as haplotypes in each group and subgroup which subdivided according to gender or age. Results Two intronic polymorphisms 89+104 c>t and 322-110 (6a)>5a were identified. The allele frequency of 89+104 t was decreased in stroke cases. The protective effect seems to be more pronounced in subgroups of female patients and age > 60 years. Also, we have confirmed decreased LDL-C level and reduced hypertension and hypercholesterolemia in 89+104 t allele carriers. In contrast, the 322-110 (6a)>5a genotype distribution was similar between cases and controls. However, the haplotype 89+104 c>t/322-110 (6a)>5a was related with LVD and SVD stroke. The haplotype c-5a was more frequent in both LVD and SVD groups while t-6a was more frequent in controls. Conclusion Ngb polymorphism 89+104 t had protective effects on LVD and SVD in the Southern Chinese Han population. A "hitchhiking" effect was observed for the 89+104 t/322-110 (6a) genotype combination especially for LVD.